The Drying Peace–Athabasca Delta, Canada: Review and Synthesis of Cryo-Hydrologic Controls and Projections to Future Climatic Conditions - Spyros Beltaos (Sustainability, 2023)
The Peace–Athabasca Delta (PAD) in northern Alberta, Canada is one of the world’s largest inland freshwater deltas, home to large populations of waterfowl, muskrat, beaver, and free-ranging wood bison. The delta region has been designated a Ramsar wetland of international importance and is largely located within the Wood Buffalo National Park, itself being a UNESCO World Heritage Site. Indigenous residents have depended on the delta for centuries to sustain their culture and lifeways. In the past five decades, the PAD has experienced prolonged dry periods in-between rare floods, accompanied by reduction in the area covered by lakes and ponds that provide habitat for aquatic life. Recharge of the higher-elevation, or “perched”, basins depends on overland flooding generated by major spring ice jams that occasionally form in the lower reaches of the Peace and Athabasca Rivers and in their various distributaries. Indigenous Traditional Knowledge and Historical Records for the unregulated Athabasca River are relatively scarce, but conclusively demonstrate the role of ice jams in replenishing perched basins of the Athabasca sector of the PAD. Similar information, coupled with extensive hydrometric and observational data for the regulated Peace River have enabled elucidation of the physical mechanisms that lead to ice-jam flooding of the Peace sector and assessment of regulation impacts on flood frequency. Such understanding can inform design of remedial strategies to moderate or arrest the drying trend of the delta. Climate-related projections to future scenarios suggest reduced frequency of ice-jam floods, albeit with uncertainty.